Kiai in Indonesian Social-Political Changes - Yanto Bashri (Lakpesdam PCNU Kota Salatiga, 2021)
This article describes the existence of kiai khos, a group of new traditional elites, who are able to play significant roles not only in the religious field but recently also in socio-political issues. These roles are served as the manifestation of their mastery of classical books (kitab kuning). Since KH. Abdurrahman Wahid (Gus Dur) during his presidency, 1999-2001, the term kiai khos has become a new prototype for kiai with not only religious abilities but classical book mastery. The study shows that these new traditional elites have transformed the pesantren into a dynamic and are able to encourage kiai and santri to move forward well in the context of politics, economics and religion. It was done by using qualitative ethnographic methods with a socio-anthropological approach explaining the new space of traditional elites as a result of their imaginative articulation in the dynamics of religion and politics in Indonesia.